Analysis of Pyrazine Compounds of Sauce-flavor Baijiu from Different Regions - Ling XIANG; Qixiao WU; Junjie JIA; Mansi NIU; Tingyao TU; Long MA; Rongkun TU; Songtao WANG; Caihong SHEN (Shipin gongye ke-ji)
Pyrazines are the flavor component basis of the baking aroma of sauce-flavor baijiu and are also an important index for evaluating differences in quality. To explore differences in pyrazine content in sauce-flavor baijiu from different regions, liquid chromatography-tandem mass spectrometry (LC-MS/MS), sensory evaluation and orthogonal partial least squares discriminant analysis (OPLS-DA) were used to identify 16 pyrazines in 69 sauce-flavor baijiu products from Sichuan, Guizhou, and other regions. No significant differences were found in pyrazines identified in sauce-flavor baijiu from different regions, but significant quantitative differences in content were found. Average pyrazine content in sauce-flavor baijiu in Guizhou (26472.53 μg/L) was higher than that in Sichuan (18544.17 μg/L) and other regions (16495.45 μg/L), and tetramethyl pyrazine was found in the highest proportion of the 69 sauce-flavor baijiu products, and the content ranged from 64.81 to 50399.56 μg/L. The key aroma substances in sauce-flavor baijiu, 2-ethyl-3,5-dimethylpyrazine, 2-ethyl-3,6-dimethylpyrazine, 2,6-dimethylpyrazine, and trimethylpyrazine had odor activity values (OAV) >1 in the 69 sauce-flavor baijiu products. Tetramethylpyrazine, trimethylpyrazine, 2-ethyl-6-methylpyrazine, 2,3-dimethylpyrazine and 2-ethyl-3,5-dimethylpyrazine were selected by OPLS-DA as the main difference of pyrazine compounds in different places to distinguish sauce-flavor baijiu (VIP>1). The sensory quantitative results showed that there were differences in the sensory properties of burnt aroma, baked aroma, paste aroma, grass aroma, earth aroma, green leaf or vegetable aroma and nutty aroma. The results of this study provide an important reference for regional differentiation and brewing process regulation of sauce-flavor baijiu.